Policy analysis of water resources and irrigation management for strengthening food security in Indonesia - Andi Setyo Pambudi; Bambang Pramujo (Universitas Pakuan, 2025)
Indonesia is still classified as a country with a relatively high population growth rate. Economic growth embodied in increased industrial, service, and urban activities requires support from various sectors, including raw water supply. Water resources for food security are related to irrigation's quantity, quality, and accessibility. Irrigation development can take the form of new infrastructure development, maintenance, and protection of the irrigation water source area. The strategic issue of irrigation as a follow-up from this, cannot be separated from the problem of competition in water allocation, the burden of irrigation service costs, and local political issues regarding water control at the site level. On a policy scale, water resource management for food security requires strengthening regulations, political will, land-use change management, coordination, and adequate funding from the central to regional levels according to their respective authorities. This paper attempts to analyze irrigation development policies in the context of water resources development which aims to provide input on food security policies in Indonesia. This study uses qualitative methods through literature studies on water resources management for food security in Indonesia. The literature review method is based on five principal regulations, ten papers, and government reports. The analysis result recommends food security in the irrigated agriculture sector with strategies to increase production capacity and expand services of irrigation networks. Problems with irrigation water availability can be anticipated by conserving upstream watersheds, optimizing and normalizing reservoirs, and building dam infrastructure as water reservoirs for supplies throughout the planting period. Policies related to water resources affect food security through increasing agricultural production, diversifying production (sufficient water availability supports non-rice farming), reducing the risk of dry seasons, increasing resilience to climate change, and reducing water conflicts. Ensuring sustainable food security demands immediate resolution of irrigation challenges through comprehensive water resource management strategies including upstream conservation, reservoir normalization, infrastructure development, improved governance, and community participation.